104th Fresno County Bar Association Annual Bar Banquet-TorNino's - Watkins, Howard::::::::: (1986)
Justice Hollis Best and former Fresno County Counsel Robert Wash; Lee Snyder talking with Fresno County Counsel Max Robinson and James Waterman on far right Table settings of eight